Future direction of urban planning education: the Malaysian universities-industry experience - Zahari, Rustam Khairi; Raja Ariffin, Raja Noriza; Ngah, Ibrahim; Syed Subli, Syed Mohd Hassan; Mohd @ Ahmad, Ibrahim; Abdul Aziz, Norsiah (International Academy of Technology, Education and Development (IATED), 2017)
Rapid urbanization is a common global phenomenon and Malaysia is not an exception with more than 75 percent of its population currently living in urban centres. One way of addressing urbanization challenges is through institutions producing competent urban planners with the industry playing a vital role in the design and implementation of the universities’ curriculums. The objective of this study is to investigate the perceptions and expectations of the industry on urban planning programs of Malaysian universities. The inputs from the industry were collected through a survey involving respondents from government agencies, urban planning practitioners, built environment consultants and property developers.